Disseminated opportunistic infections masquerading as central nervous system malignancies - Ossama Tawfik; Amira Hassan; Wael Mohamed; Cynthia Essmyer; Eric Ewing; Vincent Lem; Bartosz Grobelny; Jonathan Breshears; Naveed Akhtar (Elsevier, 2022)
Central nervous system manifestations are not only rare but extremely challenging to diagnose in patients with disseminated opportunistic infections. These CNS presentations can be very non-specific. On rare occasions, they can present as space-occupying lesions raising suspicions of primary or metastatic tumors. In this manuscript, we report a series of three cases of disseminated opportunistic infections with space-occupying lesions in the brains that are extremely challenging to diagnose. We are reporting a series of three cases of disseminated opportunistic infections with intracranial space-occupying lesions that were extremely challenging to diagnose; two patients with disseminated toxoplasmosis and one with disseminated nocardiosis. The clinicopathologic findings, radiological studies, and important diagnostic tests are discussed along with a review of the literature.